قراءة في مؤشرات تقرير التنافسية العالمي للجزائر خلال الفترة 2010-2018. - راشي طارق (My University, 2020)
يهدف هذا البحث إلى متابعة وتحليل مؤشرات التنافسية للجزائر ضمن تقرير التنافسية العالمي خلال الفترة 2010-2018، وذلك بدراسة تطور أهم المؤشرات المعبرة والتي يحددها التقرير في ثلاثة محاور أساسية هي المتطلبات الأساسية، ومحفزات الكفاءة، وتطور الاعمال والإبتكار من خلال الإعتماد على 12 معيار ينضوي تحت كل معيار مجموعة مؤشرات فرعية. وبالتالي، فإن هذه الدراسة تسعى إلى كشف أهم التطورات على المؤشرات التي حققت فيها الجزائر تقدما مع تبيان أهم الإخفاقات التي مست بعض المؤشرات ضمن تقرير التنافسية العالمي للفترة 2010-2018 في محاولة من أجل مساعدة متخذي القرار على تقييم السياسات والبرامج والإجراءات التي أنتهجتها الجزائر من أجل الوقوف على نقاط القوة وكيف يمكن العمل على إستدامتها و كشف نقاط الضعف من أجل معالجتها. ولمعالجعة هذا البحث أملت طبيعة الموضوع إعتماد المنهج الوصفي والتحليلي من خلال متابعة وتحليل أهم المؤشرات المعبرة عن الأداء التنافسي للجزائر وفق ما تحددها مؤشرات تقرير التنافسية العالمي خلال الفترة 2010-2018. وتوصل هذا البحث إلى نتائج أهمها تسجيل تدهور لأهم المؤشرات بداية من 2011 إلى غاية 2013 ليليها تحسن وتعافي بطيئ للمؤشرات خلال الفترة 2014-2017 بإستثاء مؤشر بيئة الاقتصاد الكلي الذي سجل تطور مهم إلى غاية 2014 وبعدها بدأ في التدهور ليسجل أسوء مرتبة له سنة 2018. كما أن سنة 2018 سجلت الجزائر تراجع في الترتيب على مؤشر التنافسية بـ 6 مراتب. This paper aims to follow up and analyze competitiveness of the Algeria during the period 2010-2018 within the Global Competitiveness Reports, by examining the development of the most important indicators expressed in the report in three main axes: basic requirements, efficiency incentives, business development and innovation through the adoption of 12 criteria that fit under each criterion sub-indices. Therefore, this study seeks to uncover the most important developments on the indicators in which the Algeria has made progress with the most important failures. Some indicators were included in the Global Competitiveness Report 2010-2018 in an attempt to help decision makers evaluate the policies, programs and procedures adopted by the Algeria in order to identify strengths and how to sustain them and to identify weaknesses in order to address them. In order to deal with this research, the nature of the subject and the method of its presentation dictated the adoption of the descriptive and analytical approach through follow-up and analysis of the most important indicators reflecting the competitive performance of the Algeria as determined by the indicators of the Global Competitiveness Report 2010-2018. This research found the most important indicators from 2011 to 2013, followed by improvement and slow recovery during the period 2014-2017, except for the macroeconomic environment index, which recorded a significant development until 2014 and then began to deteriorate to register its worst in 2018. Algeria also recorded decline in the ranking on the index of competitiveness year by 6 ranks.